Refugee return and social cohesion - Ruiz, I; Vargas-Silva, C (Oxford University Press, 2022)
Refugee return often involves the re-encounter of individuals who were separated for years, but we know little about its impact on social cohesion. We explore this impact using data from a nationwide survey that we conducted in Burundi, a country that experienced high levels of repatriation during the 2000s. We find that refugee return has a negative impact on the feeling that community members help each other, could borrow money for emergencies from non-household members, and the feeling that the community is peaceful. The impacts on measures of reconciliation, post-conflict justice, trust, and participation in community groups are mostly statistically insignificant. We also explore how these effects differ across different sub-samples based on ethnic composition, pre-war land scarcity, and attitudes towards return. The results highlight the possible role of new migration-related societal divisions in affecting post-return social cohesion.